Dynamic and diverse sugar signaling. (October 2016) - Li, Lei; Sheen, Jen
Highlights: Emerging sugar signals are discussed. Direct sugar sensing and signaling is triggered via sugar-binding sensors. Sugar-derived metabolites modulate energy sensors and indirectly relay signaling. Comparative transcriptome profiles highlight the dynamic and diverse sugar responses. Abstract : Sugars fuel life and exert numerous regulatory actions that are fundamental to all life forms. There are two principal mechanisms underlie sugar 'perception and signal transduction' in biological systems. Direct sensing and signaling is triggered via sugar-binding sensors with a broad range of affinity and specificity, whereas sugar-derived bioenergetic molecules and metabolites modulate signaling proteins and indirectly relay sugar signals. This review discusses the emerging sugar signals and potential sugar sensors discovered in plant systems. The findings leading to informative understanding of physiological regulation by sugars are considered and assessed. Comparative transcriptome analyses highlight the primary and dynamic sugar responses and reveal the convergent and specific regulators of key biological processes in the sugar-signaling network.